Understanding the influence of epistemological beliefs on the creative learning process. Issue 4 (2nd October 2021) - Ho, Amic G.
ABSTRACT: The creative process is a process that includes many elements that provide solutions for problems that occur in everyday life. While the nature of creativity is changing, creative participants are also inevitably required to be problem solvers. They have to interpret and clarify problems by utilizing creative thinking. Therefore, problem-based research is an approach that provides a systematic set of guidelines for junior creative arts students to investigate, examine and execute learned concepts as well as solve problems practically. Although problem-based research is commonly applied, some junior creatives still do not engage with or even perform well with this approach. Their process of understanding and organizing information may be influenced by the inadequate epistemological beliefs of the junior creative arts students. This study aims to investigate the influence of inadequate epistemological beliefs on the learning processes of junior creative arts students. A pilot study was conducted for comparing the junior creative arts students' performance in an authentic situation.